PREDATION AND OTHER MORTALITY FACTORS in GRASSHOPPER POPULATIONS - Mook, Leonard (My University, 1960)
A study of two grasshopper populations at low densities has shown the relative influence of climate, parasites and predators on the mortality of the nyaphal and adult stages. Short term weather fluctuations have a large influence on the mortality, but cannot control a population. Parasites were scarce and of small importance. Predators played an important role in the control of grass hopper populations at low densities. A special study has been made of the praying mantis-grasshopper relationship.